Pengaruh Kualitas Sumber Daya Manusia dan Efektivitas Kerja Terhadap Kinerja Pegawai Pada Badan Standardisasi Instrumen Pertanian Sulawesi Selatan - Andi Hamzah Makmur (International Forum of Researchers and Lecturers, 2025)
Andi Hamzah Makmur, 2024. The Effect of Human Resources Quality and Work Effectiveness on Employee Performance at the South Sulawesi Agricultural Instrument Standardization Agency. Employee Performance at the South Sulawesi Agricultural Instrument Standardization Agency. Thesis Management Study Program, College of Management Sciences, Institute of Education Indonesia (STIM-LPI) Makassar which is supervised by Dr. Ir. Andi Nuryadin, SE., M.Si. and Ansar Mulkin Bas, S.E., M.M. This research aims to determine the effect of Human Resources Quality and Work Effectiveness on Employee performance. The object of this research is the Agricultural Instrument Standardization Agency South Sulawesi. The type of research used is quantitative research quantitative research by distributing questionnaires via google from. Sampling using saturated sample technique. The results of this study shows that the partial test of the Quality of Human Resources has a significant effect of 0.000 or below 0.05 while the Effectiveness of Human Resources has a significant effect of 0.000. significant influence of 0.000 or below 0.05 while Work Effectiveness also has a strong influence on Employee Performance but Work Effectiveness also has a strong influence on Employee Performance, however when compared between the Quality of Human Resources and Work Effectiveness.